Pengaruh Keimanan, Pengetahuan, Akuntabilitas, dan Transparansi terhadap Motivasi Muzakki Membayar Zakat : Studi kasus di Lembaga Amil Zakat Kota Bandar Lampung - Jaka Darmawan (Penerbit Goodwood, 2023)
Purpose: The objective of this research was examining and analyzing the factors affecting muzakki (zakat donators) motivation to pay zakat in the Zakat Agency, Bandar Lampung. Method: The sampling technique used in this research was the accidental sampling. The sample of this research was muzakki (zakat donators) paying zakat in Zakat Agency, Bandar Lampung. The data analysis technique used in this research was the multiple regression. Result: The result of this research showed that the understanding and the accountability of zakat had a significant effect on muzakki motivation to pay zakat; however, the level of faith and the financial report transparency did not significantly affect the muzakki motivation to pay zakat.